Fate of fluoroquinolones associated with antimicrobial resistance in circular periurban agriculture - Prack McCormick, Barbara (2024)
Animal antibiotic use contributes to antimicrobial resistance (AMR) in humans. While animal manure benefits soil fertility, it also acts as hotspot for antibiotic residues, antibiotic-resistant bacteria, and their genes. Amending soils with poultry litter is recognized as “magic” among horticulture farmers and it remains a common practice globally. However, this poses a risk especially in countries where prophylactic use of antibiotics is allowed. InArgentina, fluoroquinolones are used in this way besides being listed as essential medicines and classified as “watch” by the World Health Organization. Antibiotic selective pressure can favour AMR in the environment but the fate of antibiotic residues and AMR dissemination from these practices remains poorly understood. Our research addresses this gap with a biological model tracing fluoroquinolones from poultry to soil to lettuce andtracking anthropogenic AMR with the proposed biomarker genes sul1 and intI1. Fresh poultry litter was stored for six months before application in a horticulture field experiment. The experiment included control and manured plots where lettuce was cultivated till harvest. Enrofloxacin concentration was 7.3 μg/kg in fresh poultry litter, while its metabolite ciprofloxacin was 39.22 μg/kg after storage. Although no fluoroquinolones were detected in soils, lettuce from manured plots contained enrofloxacin and ciprofloxacin at 14.97 and 9.77 μg/kg, respectively, providing evidence of fluoroquinolone bioaccumulation in plants. Abundance of sul1 and intI1 in poultry litter was not affected by storage. Manured soils showed better soil quality than controls, but sul1 gene abundance was 1.6 times higher, reaching 7.61 Log sul1/g soil. A less sensitive, but significant effect was registered for intI1. These findings show that static storage is insufficient to stop the transmission of antibiotics and AMR biomarkers from poultry to horticulture. Amending soil with industrial poultry litter contributes to pollution with these emergent contaminants and risks human antibiotic exposure through fresh vegetables.